A Renewable Energy Pool brings benefits of energy transition to consumers - Karsten Neuhoff; Mats Kröger; Leon Stolle (DIW Weekly Report, 2024)
German companies view high and uncertain electricity prices a major challenge. A Renewable Energy Pool (RE-Pool), wherein the favorable conditions of competitive tenders for new wind and solar power projects are passed on to electricity consumers, could hedge such price risks. Consumers' electricity prices are thus hedged for the share of their consumption that corresponds to the RE-Pool's generation profile. This, in turn, strengthens the incentives to invest in flexibility, such as in heat storage systems or batteries, in order to adjust their demand to wind and solar electricity production in the pool. In addition, the RE-Pool profile can serve as a reference against which new products to hedge flexibility can be introduced in the futures and forward markets. The RE-Pool also addresses financing risks linked to regulatory uncertainties faced by renewable energy projects. This reduces financing costs and thus costs for consumers and enhances confidence in future renewable deployment and thus supports investments into the supply chain of project developers and manufacturers. The RE-Pool contributes to an even better use of renewable energy sources in the energy supply and prepares the electricity system for a future powered by a greater share of renewable energy.
Keywords: L94; Q48; Q41; 330; Renewable Energy Policy; Electricity Markets; Flexibility